If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = x + -4 Reorder the terms: 7 + 5x = x + -4 Reorder the terms: 7 + 5x = -4 + x Solving 7 + 5x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 5x + -1x = -4 + x + -1x Combine like terms: 5x + -1x = 4x 7 + 4x = -4 + x + -1x Combine like terms: x + -1x = 0 7 + 4x = -4 + 0 7 + 4x = -4 Add '-7' to each side of the equation. 7 + -7 + 4x = -4 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = -4 + -7 4x = -4 + -7 Combine like terms: -4 + -7 = -11 4x = -11 Divide each side by '4'. x = -2.75 Simplifying x = -2.75
| 176=(15-2x)(12-2x)x | | 6x^2+1.5-13.5=0 | | 4(6x-33)=72 | | y=-(1/32)(x+1)^2+4 | | 192*5/8 | | 33=((2x)^2)/((0.06-x)(0.03-x)) | | 5a+16=51 | | (6x-36)=9 | | 2(4+1)+6=20-3(4) | | y=2/17x | | 4(6x-36)=9 | | t+8/10=9/10 | | X^2=5x+10 | | 9x+-4(x+-2)=x+20 | | 1.8d+31=3.4d+9 | | 0.2n-4.1=1.2n-2.3 | | -3(w-7)=-7w+17 | | s^2-11s+24= | | (-4.9x^2)-7x+450=0 | | 9x-4(x-2)=20 | | 15x^3y-20xy+5x^3=5x | | (x^2)-7x+450=0 | | 3x/4-21x/33-1/1/8= | | 4w-7=-35 | | 3x+7=3x-10 | | 54/15 | | a^2+7a=144 | | 8*x+10+2x+4*x+8-6=14x+36 | | V-8=4 | | 4/5b^2=44 | | (X^9/7)^7 | | 2m^2=44 |